1998
DOI: 10.1128/jvi.72.6.4694-4703.1998
|View full text |Cite
|
Sign up to set email alerts
|

CD4-Induced Conformational Changes in the Human Immunodeficiency Virus Type 1 gp120 Glycoprotein: Consequences for Virus Entry and Neutralization

Abstract: Human immunodeficiency virus type 1 (HIV-1) entry into target cells involves sequential binding of the gp120 exterior envelope glycoprotein to CD4 and to specific chemokine receptors. Soluble CD4 (sCD4) is thought to mimic membrane-anchored CD4, and its binding alters the conformation of the HIV-1 envelope glycoproteins. Two cross-competing monoclonal antibodies, 17b and CG10, that recognize CD4-inducible gp120 epitopes and that block gp120-chemokine receptor binding were used to investigate the nature and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(96 citation statements)
references
References 73 publications
(104 reference statements)
2
92
0
2
Order By: Relevance
“…Past investigations on the influence of the V1V2 loop on steering neutralization activity have been restricted to few, mostly highly neutralization-sensitive isolates (HxB2, LAI, SF162, R3A, and YU-2; Wyatt et al, 1993, 1995; Cao et al, 1997; Stamatatos and Cheng-Mayer, 1998; Stamatatos et al, 1998; Sullivan et al, 1998; Saunders et al, 2005; Laakso et al, 2007; Bontjer et al, 2009) and thus left a definite verdict on the potency of the V1V2 loop shielding effect against primary viruses pending. In this study, we generated a panel of six infection-competent V1V2 loop–deleted Env’s of tier 1 (NL4-3 and SF162), tier 2 (JR-FL*, RHPA, and REJO), and tier 3 (ZA110.c10.14) subtype B isolates by inserting the linker sequence Asp-Ala-Gly (DAG) as described previously (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Past investigations on the influence of the V1V2 loop on steering neutralization activity have been restricted to few, mostly highly neutralization-sensitive isolates (HxB2, LAI, SF162, R3A, and YU-2; Wyatt et al, 1993, 1995; Cao et al, 1997; Stamatatos and Cheng-Mayer, 1998; Stamatatos et al, 1998; Sullivan et al, 1998; Saunders et al, 2005; Laakso et al, 2007; Bontjer et al, 2009) and thus left a definite verdict on the potency of the V1V2 loop shielding effect against primary viruses pending. In this study, we generated a panel of six infection-competent V1V2 loop–deleted Env’s of tier 1 (NL4-3 and SF162), tier 2 (JR-FL*, RHPA, and REJO), and tier 3 (ZA110.c10.14) subtype B isolates by inserting the linker sequence Asp-Ala-Gly (DAG) as described previously (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the antigenbinding fragment (Fab) and single-chain fragments of these CD4i-specific monoclonal antibodies do have neutralizing function 58,60 . The inability of the whole IgG CD4i-specific monoclonal antibody to neutralize can be explained by steric hindrance, given that the distance between the CD4i epitope on gp120 and the target cell membrane in molecular models seems too small to accommodate the entire IgG molecule 61,62,132 . If these observations are confirmed, the physical constraints on antibody access to the CD4i epitope will preclude the use of antibodies to this epitope as a barrier against infection with HIV-1.…”
Section: Antibodies To the Cd4-induced Epitope Of Gp120mentioning
confidence: 99%
“…This could be explained by the fact that primary HIV-1 isolates are much less sensitive to neutralization by sCD4 than are laboratory-adapted HIV-1 strains, probably resulting from the lower affinity for CD4 and the reduced sCD4-induced gp120 shedding from the virions [23][24][25]. In addition, several reports demonstrated that soluble CD4 could activate the envelope glycoprotein gp120, making it competent to interact with the coreceptor, and thus could promote fusion/entry [22,26,27].…”
Section: Introductionmentioning
confidence: 99%